2008
DOI: 10.1097/jom.0b013e31815d88e2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma and Occupation in Men: A Case-Control Study

Abstract: Our findings suggest an association between metal machining jobs and hepatocellular carcinoma, although we cannot rule out the possibility that it was observed by chance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Several studies ascertained occupation and industry information from a national supplemental pension fund, interviews, and questionnaires [44, 46, 5052]. Some studies coded occupational information using classification systems such as the International Standard Classification of Occupations and the International Standard Industrial Classification of All Economic Activities [44, 46, 50].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies ascertained occupation and industry information from a national supplemental pension fund, interviews, and questionnaires [44, 46, 5052]. Some studies coded occupational information using classification systems such as the International Standard Classification of Occupations and the International Standard Industrial Classification of All Economic Activities [44, 46, 50].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies coded occupational information using classification systems such as the International Standard Classification of Occupations and the International Standard Industrial Classification of All Economic Activities [44, 46, 50]. Job titles were typically defined as farmer, farm worker, and farm laborer, and industries as agriculture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Workers exposed to solvents, toluene or xylene were also associated with primary liver cancer [19,52]. Recently, a case-control study suggested a mild association between metal machining jobs and HCC among those without viral infection [53]. Nevertheless, a multicenter international liver tumor study failed to establish the association between occupational exposures and liver cancer among women, even though the viral factor was carefully considered and occupation-exposure matrix was constructed [54].…”
Section: Discussionmentioning
confidence: 99%